The Relationship Between Thrombophilia and Modifications in First-Trimester Prenatal Screening Markers - Viorela Romina Murvai; Casandra-Maria Radu; Radu Galiș; Timea Claudia Ghitea; Anca-Florina Tătaru-Copos; Alexandra-Alina Vesa; Anca Huniadi (Medicina)
Background and Objective: Thrombophilia significantly increases the risk of complications like recurrent pregnancy loss, preeclampsia, IUGR, and stillbirth. Objective: This study aimed to evaluate the impact of inherited thrombophilic mutations on first-trimester screening outcomes, focusing on their relationship with maternal biomarkers and ultrasonographic parameters. Materials and Methods: A prospective observational study was conducted on 105 pregnant women during the first trimester (10–13 weeks of gestation). Genetic testing identified common thrombophilic mutations, including factor V Leiden, prothrombin G20210A, and MTHFR polymorphisms. First-trimester screening parameters, including PAPP-A, free β-hCG, and nuchal translucency (NT), were assessed. Maternal demographic and clinical characteristics, such as parity and smoking status, were recorded. Pearson correlation and risk estimates were calculated to explore associations between thrombophilic mutations, maternal factors, and screening results. Results: Lower parity (≤2) was significantly associated with a reduced risk of low PAPP-A levels (<1.0 MoM) (OR = 0.173; 95% CI: 0.044–0.676). Non-smokers showed a trend toward lower risk of low PAPP-A, although the association was not statistically significant. NT measurements <2.5 mm were consistent with normal fetal development, while maternal factors such as chronic hypertension and a history of small-for-gestational-age infants showed no significant correlations with screening markers. No significant association was observed between thrombophilic mutations and biomarker levels. Conclusions: Parity emerges as a significant factor influencing first-trimester screening outcomes, particularly PAPP-A levels, underscoring the need for tailored risk assessments in multiparous women. While smoking and thrombophilic mutations showed no definitive impact, their potential role in placental dysfunction warrants further investigation. These findings emphasize the importance of integrating maternal characteristics into screening protocols to enhance predictive accuracy and maternal–fetal outcomes.